A taxonomic revision of the Neotropical termite genus Rhynchotermes (Isoptera, Termitidae, Syntermitinae) - Constantini, Joice P.; Cancello, Eliana M. (Zootaxa, 2016)
We herein revise the taxonomy of the Neotropical syntermitine genus Rhynchotermes Holmgren. Seven species were recognized and diagnosis given for all available castes. This includes two new species: Rhynchotermes amazonensis Constantini & Cancello sp. nov. and Rhynchotermes matraga Constantini & Cancello sp. nov. Rhynchotermes guarany Cancello is recognized as syn. nov. of Rhynchotermes nasutissimus (Silvestri) and Rhynchotermes nyctobius Mathews syn. nov. of Rhynchotermes diphyes Mathews. The three other formerly described species include Rhynchotermes perarmatus (Snyder), Rhynchotermes piauy Cancello and Rhynchotermes bulbinasus Scheffrahn. We also provide a key to the soldiers of the genus, a distribution map of the species as well as illustrations and biological notes for all species.